PENGARUH PERPUTARAN MODAL KERJA, UKURAN PERUSAHAAN, LEVERAGE DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN ANIMAL FEED DI BEI PERIODE 2012-2015 - AYU PUSPITA, DEBBY (Jurnal Ilmu Manajemen (JIM), 2018)
Manufacturing companies profitability in Indonesia were affected by financial factors which can be measured from financial ratio. The aim of this study is to analyze whether variables such as working capital turnover, firm size, leverage and liquidity have an influence on corporate profitability as measured by using ROA. Population in this study is Animal Feed companies which listed in IDX to quarterly period of 2012-2015, that are 4 companies. Sample was taken using saturated sampling method, because amount sample under 30 or for research that wants to make generalizations with low error rate. Data analysis techniques in this study using the classical assumption test, multiple linear regression analysis and hypothesis testing. The data obtained will then be calculated using SPSS. The results showed that there are 2 variables that Working Capital Turnover and Liquidity have a significant positive influence on profitability. Conversely variable Firm Size has a significant negative influence on profitability. As for the leverage variable has no significant effect on profitability. These results show that only variable of Working Capital Turnover and Liquidity are high influence in the achievement of profit at Animal Feed company which listed in IDX to quarterly period of 2012-2015 Keyword: Working Capital Turnover, Firm Size, Leverage, Liquidity, Profitability